The Two Classes of Ceramide Synthases Play Different Roles in Plant Immunity and Cell Death - Zeng, Hong-Yun; Bao, He-Nan; Chen, Yi-Li; Chen, Ding-Kang; Zhang, Kun; Liu, Shuai-Kang; Yang, La; Li, Yong-Kang; Yao, Nan (Frontiers in Plant Science, 2022)
Ceramide synthases (CSs) produce ceramides from long-chain bases (LCBs). However, how CSs regulate immunity and cell death in Arabidopsis thaliana remains unclear. Here, we decipher the roles of two classes of CS, CSI (LAG1 HOMOLOG 2, LOH2) and CSII (LOH1/3), in these processes. The loh1-2 and loh1-1 loh3-1 mutants were resistant to the bacterial pathogen Pseudomonas syringae pv maculicola (Psm) DG3 and exhibited programmed cell death (PCD), along with increased LCBs and ceramides, at later stages. In loh1-2, the Psm resistance, PCD, and sphingolipid accumulation were mostly suppressed by inactivation of the lipase-like proteins ENHANCED DISEASE SUSCEPTIBILITY 1 (EDS1) and PHYTOALEXIN DEFICIENT 4 (PAD4), and partly suppressed by loss of SALICYLIC ACID INDUCTION DEFICIENT 2 (SID2). The LOH1 inhibitor fumonisin B1 (FB1) triggered EDS1/PAD4-independent LCB accumulation, and EDS1/PAD4-dependent cell death, resistance to Psm, and C16 Cer accumulation. Loss of LOH2 enhances FB1-, and sphinganine-induced PCD, indicating that CSI negatively regulates the signaling triggered by CSII inhibition. Like Cer, LCBs mediate cell death and immunity signaling, partly through the EDS1/PAD4 pathway. Our results show that the two classes of ceramide synthases differentially regulate EDS1/PAD4-dependent PCD and immunity via subtle control of LCBs and Cers in Arabidopsis.